Pengaruh Kualitas Tidur terhadap Nilai Hemoglobin pada Remaja Putri - Elyn Arlinda; Dyah Artini; Siti Nurhayati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Anemia is a condition where a person has a hemoglobin value below normal (12 gr/dl). The prevalence of anemia is around 30% of women of childbearing age, namely 15-49 years old, suffer from anemia. In Indonesia, data on anemia sufferers shows 32%. The prevalence of anemia in DIY shows that the results of Riskesdas in 2013 amounted to 37.1% of adolescent girls experiencing anemia, and further increased in the 2018 Riskesdas results, namely 48.9% experiencing anemia. Anemia has a negative impact on adolescent girls, namely a decrease in immune system function, easy fatigue, disrupting physical, cognitive, psychological growth and development, and reducing learning concentration which can affect learning achievement. Factors causing anemia can be caused by sleep quality. Good sleep will help the body's biological process to regenerate erythrocyte cells in producing gemoglobin. This study uses a quantitative correlation research design with purposive sampling technique with inclusion and exclusion criteria. The number of samples in this study were 30 adolescent female respondents. Statistical analysis used is chi-square with a p value <0.5. The results of this study indicate that the majority of adolescent girls experience poor sleep quality as many as 18 adolescent girls (60%) and as many as 21 adolescent girls (70%) have abnormal hemoglobin values. Chi-square test obtained a value of p = 0.001 <0.5 which means that sleep quality can affect hemoglobin levels in adolescent girls